Chasing the precursor of functional hematopoietic stem cells at the single cell levels in mouse embryos - Wang, Xiaochen; Gong, Yuemin; Ema, Hideo (Journal of Hematology & Oncology, 2016)
Adult hematopoietic stem cells (HSCs), the ideal system for regenerative research, were isolated at single cell levels decades ago, whereas studies on embryonic HSCs are much more difficult.